Divine love in the letter to the Romans - Pieter G.R. de Villiers (In die Skriflig, 2016)
This article investigates divine love in the letter to the Romans from the perspective of love as a key motif in spirituality and in light of spiritual hermeneutics. After a short introduction about the significance of love as a spiritual motif, the article motivates why the notion of divine love is important for understanding the letter to Romans. It challenges existing interpretations of love in contemporary research on Romans that associates it mostly with the relationship between people, neglecting the significant passages in Romans in which love is first and foremost associated with the character and actions of God. In the rest of the article four essential characteristics of divine love is investigated, with attention to its originary, intimate, powerful and self-giving nature.1